Neurosyphilis presenting with a stroke-like syndrome - Abkur, Tarig Mohammed (BMJ Case Rep, 2015)
Neurosyphilis results from infection of the central nervous system (CNS) by Treponema pallidum. Neurosyphilis can occur at any time after initial infection, particularly in immunocompromised patients. We describe a case of a 47-year-old man who presented with mixed dysphasia, right upper motor neuron facial palsy and right hemiparesis. Collateral history from the family revealed slowly progressive cognitive impairment and behavioural changes. Neuroimaging was unremarkable, suggesting a non-vascular aetiology. As there was no clear cause for the presentation, a lumbar puncture was performed and serum samples were sent for syphilis serology. The diagnosis of neurosyphilis was made on the basis of a positive RPR test in cerebrospinal fluid. The patient was treated with benzylpenicillin and made a full recovery, with restoration of cognitive function to baseline.